Respuesta :
Answer:
The roots of the quadratic equation are
[tex]x=-3+3\sqrt{2}[/tex]
[tex]x=-3-3\sqrt{2}[/tex]
Step-by-step explanation:
we have
[tex]x^{2} +6x-9=0[/tex]
we know that
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]x^{2} +6x-9=0[/tex]
so
[tex]a=1\\b=6\\c=-9[/tex]
substitute in the formula
[tex]x=\frac{-6(+/-)\sqrt{6^{2}-4(1)(-9)}} {2(1)}[/tex]
[tex]x=\frac{-6(+/-)\sqrt{72}} {2}[/tex]
[tex]x=\frac{-6(+/-)6\sqrt{2}} {2}[/tex]
[tex]x=-3(+/-)3\sqrt{2}[/tex]
[tex]x=-3(+)3\sqrt{2}[/tex]
[tex]x=-3(-)3\sqrt{2}[/tex]
Given equation is :
[tex]x^{2}+6x-9=0[/tex]
We will solve this quadratic equation, using the formula:
[tex]x1,2=\frac{-b+\sqrt{b^{2}-4ac}}{2a}[/tex] and
[tex]x1,2=\frac{-b-\sqrt{b^{2}-4ac}}{2a}[/tex]
Now, putting a=1 , b=6 and c =-9 we get
[tex]x=\frac{-6+\sqrt{6^{2}-4*1(-9)}}{2*1}[/tex] and
[tex]x=\frac{-6-\sqrt{6^{2}-4*1(-9)}}{2*1}[/tex]
Final solutions are: [tex]x=3(\sqrt{2}-1)[/tex] and
[tex]x=-3(\sqrt{2}+1)[/tex]